Pusat Diagnostik dan Terapi Jiwa dengan Pendekatan Arsitektur Healing Environment - Muslimah, Nurul; Wasilah, Wasilah; AS, Zulkarnain (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2022)
Abstract_ Mental health disorders are still a significant health problem in South Sulawesi example of them is in Gowa Regency. 13,7% of people with mental health disorders in the Gowa Regency. The number of people with mental disorders hospitalized at the Dadi Hospital in Makassar City as of December 31, 2018, was 665. Some are from Makassar City and spread over 23 regencies/cities. One of them is in Gowa Regency. The fact is that in Gowa Regency in 2016, cases of mental disorders reached 551 people. Still, in Gowa Regency, there were no exceptional hospitals to treat patients with mental health disorders, especially in treatment and recovery. Designing a Diagnostic and Mental Therapy Center for these problems is necessary. The method used is descriptive through literature studies, field studies, comparative studies, or precedent studies to compare buildings with the same function. The concept chosen is the Healing Environment Architectural Approach Concept which is a concept that can create an environment or space atmosphere that can support the healing process through design elements such as colors, materials, and natural factors. Keywords: Mental Health Disorders, Healing Environment Architecture, Gowa Regency.